Use of Social Networks to Inform the Population About Extraordinary Events - Jozef KUBÁS; Jozef RISTVEJ (Communications of International Proceedings, 2022)
Social networks are one of the biggest phenomena of our time. Their usefulness is not limited to communication between acquaintances, but they have a wide range of uses. Social networks can be used as a source of various information. This option is often used by public and local government authorities to inform residents about events. The article is focused on the appropriateness of the usability of social networks for informing about extraordinary events. In order to highlight the importance of information, the article is supplemented with a statistical evaluation of extraordinary events in Slovakia for the period of the five most recent years. Subsequently, the most used social networks in Slovakia are pointed out and the analyzed profiles on Facebook, which on this social network most often inform about extraordinary events and have the greatest impact on residents. The aim of the article is to point out the use of social networks as a source of information for the population in case of emergencies. With the help of a survey carried out in Slovakia, information was found about the preferred source of information and time spent on social networks. The results of the survey are intended to serve as a supporting tool in the process of selecting a suitable source for informing the population or employees in the event of a threat.
Keywords: Civil protection; quality of life; crisis management; occupational health and safety; social network.